Tracing the Abbasid Dynasty’s Role in Shaping Arabic Literature and Islamic Intellectual Identity - Ratna, Ai; Shofah, Anuri; Jamilah, Ayi Noer; Sabila, Rabbaniah; Riyadi, Agus (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This article investigates the formative role of the Abbasid Dynasty in shaping the intellectual identity of the Islamic world during the Golden Age of Arabic literature. The research is grounded in the idea that dynastic power, when aligned with cultural patronage and institutional innovation, can catalyze literary and scholarly flourishing. The Abbasid era, particularly in Baghdad, witnessed an unprecedented synthesis of classical knowledge and original thought, facilitated by the establishment of institutions such as Bayt al-Hikmah and the translation movement. Using a historical-analytical method, this study examines the sociopolitical conditions that enabled the emergence of key literary figures, the proliferation of philosophical and scientific discourse, and the development of a cosmopolitan literary culture. The findings demonstrate that the Abbasids not only preserved Greco-Roman and Persian legacies but also fostered new epistemologies through Arabic prose, poetry, and critical thought. This article contributes to the discourse by bridging literary history with sociological analysis, offering a nuanced understanding of how dynastic authority influenced intellectual production. It addresses a gap in existing scholarship by arguing that the Abbasid Dynasty’s strategic support for knowledge creation was instrumental in defining the contours of Islamic civilization. The conclusion affirms that the Abbasid patronage system laid the foundation for a transregional intellectual legacy that continues to inform contemporary Islamic thought and literary scholarship.